(untitled) (New York, 2010)
This book provides a much needed analysis of the interactions between climate change and the food system, with emphasis on how food security is likely to be affected and interventions needed to adapt to a warmer world
An ninh lương thực
Keywords: Nông nghiệp,Climatic changes,Food supply,Agriculture